Fuzzy Logic Closed Loop Control of 5 level MLI Driven Three phase Induction motor - Mulukutla Venkata Subramanyam; P.V.N. Prasad; G.Poornachandra Rao (International Journal of Power Electronics and Drive Systems (IJPEDS), 2013)
This paper deals about fuzzy logic control of closed loop controlled five level Multi Level Inverter (MLI) driven three phase induction motor. Three phase Induction motor is most widely used drive in Industries, so needs proper control of speed. Induction motor is fed from five level multilevel inverter which is controlled by fuzzy logic. The closed loop consists of two loops. First inner loop is current loop and second outer loop is speed loop. The torque is varied at different times and corresponding change in speed and Total Harmonic Distortion (THD) is observed. The MLI is controlled by Sinusoidal Pulse Width Modulation (SPWM) Technique.DOI: http://dx.doi.org/10.11591/ijpeds.v3i2.3062